Dharmaning Brahmana dalam Geguritan Yadnya Ring Kuruksetra - Juliana, I Wayan (Jurnal Penelitian Agama Hindu, 2025)
This research is motivated by the lack of studies on the transfer of the Aswamedha Parwa text into Geguritan Yadnya Ring Kuruksetra (GYRK), especially from the perspective of brahmana ethics, amidst the rampant transformation of Balinese literature that often ignores the moral dimension. The purpose of the research is to analyze the representation of brahmana dharma and the concept of lascarya (sincerity) in GYRK, and to revitalize the philosophical values ​​of Balinese Hinduism through a hermeneutic approach. The method used is textual hermeneutic analysis from the perspective of Hindu literature and philosophy. Primary data are taken from the GYRK and Aswamedha Parwa texts, while secondary data include brahmana ethics literature such as Sarasamuscaya and Agastya Parwa. The results of the study show that Tri Kaya Parisudha (thoughts, speech, deeds) and lascarya are actualized through the actions of four brahmanas who face moral dilemmas, such as food sacrifices in conditions of famine. The transformation of yadnya from a horse sacrifice ritual to a social sacrifice reflects the adaptation of Balinese Hindu ethical values ​​to the challenges of modernization, such as individualism and poverty. Conflicts between characters in the text are resolved through spiritual integrity, such as sewaka dharma (sincere devotion) that goes beyond formal obedience. The conclusion of the study confirms that GYRK not only revitalizes traditional philosophical values, but also becomes a medium for intergenerational ethical dialogue, bridging local wisdom with modern demands through the holistic actualization of dharma. This study contributes to the study of religious literature with a hermeneutic analysis model that integrates text, context, and philosophy, while also offering an adaptive ethical paradigm in responding to global moral degradation.